Prevalence and risk factors of posttraumatic stress disorder in COVID-19 (2023)
Posttraumatic stress disorder (PTSD) has a prevalence of 2%–5% in the general population. COVID-19 is regarded as a traumatic agent that can increase the prevalence of this disorder to up to 30%. A documentary review was thus conducted, which included 13 studies on the presence of PTSD in patients who have survived COVID-19 infection and the possible associated factors. Female and young age, as well as other aspects associated with economic losses or living alone, could influence the appearance of this psychological sequela. A preventive mental healthcare program could be implemented during infection in such patients with COVID-19 who show the characteristics described in most studies.